Differentiation of three varieties of zingiber officinale rosc. by rapd fingerprinting - Muda, M.A.; Ibrahim, H.; Khalid, Norzulaani (Faculty of Science, University of Malaya, 2004)
The genetic variation between three varieties of Zingiber officinale Rose. was investigated using Random Amplified Polymorphic DNA (RAPD) analysis. The varieties are reported to be useful in traditional medicine and food flavours in Peninsular Malaysia. Analysis was carried out on the RAPD profiles generated by 16 arbitrary primers to determine genetic differences between the varieties. The clearest polymorphic bands were obtained from OPA1, OPA8, OPA9, OPA10, OPA13, OPA16 and OPA20 primers. A total of 104 bands were scored and analysed.